Migration Distance and Body Condition Influence Shorebird Migration Strategies and Stopover Decisions During Southbound Migration - Anderson, Alexandra M.; Duijns, Sjoerd; Smith, Paul A.; Friis, Christian; Nol, Erica (Frontiers in Ecology and Evolution, 2019)
Technological constraints have limited our ability to compare and determine the proximate and ultimate drivers of migratory behaviour in small-bodied birds. Small VHF transmitters (< 1.0 g) paired with automated radio telemetry allowed us to track the movements of six small shorebird species and test hypotheses about migratory behavior in species with different migration distances. We predicted that during southbound migration, species with longer migration distances (> 9,000 km; pectoral sandpiper, Calidris melanotos, and white-rumped sandpiper, Calidris fuscicollis) would be more likely to migrate with characteristics of a time-minimizing migration strategy compared to species migrating intermediate distances (5,000-7,500 km; semipalmated sandpiper, Calidris pusilla; and lesser yellowlegs, Tringa flavipes) or shorter distances (~5,000 km; least sandpiper, Calidris minutilla; semipalmated plover, Charadrius semipalmatus), which would migrate with more characteristics of an energy-minimizing strategy. Our results indicate that migration and stopover behaviours for adults matched this prediction; longer distance migrants had longer stopover lengths, departed with higher relative fuel loads, flew with faster ground and airspeeds, and had a lower probability of stopover in North America after departing the subarctic. The predicted relationship between migration distance and migratory strategy was not as clear for juveniles. Despite our prediction that longer distance migrants would be less wind selective at departure and fly into headwinds en route, all species and age classes departed and migrated with supportive winds. Birds with higher estimated fuel loads at departure were less likely to stop in North America after departing the subarctic, indicating that some birds attempted non-stop flights from the subarctic to the Caribbean or South America. Additionally, within species, adults with higher relative fuel loads at departure had a higher detection probability after departing the subarctic, which we interpret as evidence of higher survival compared to juveniles. This study shows that migratory behaviour of shorebirds has predictable patterns based on migration distance that are moderated by body condition of individuals, with potential implications for fitness.